Haemorrhoidal haemodynamic changes in patients with haemorrhoids treated using Doppler-guided dearterialization. Issue 2 (11th April 2021) - Parello, A; Litta, F; De Simone, V; Campennì, P; Orefice, R; Marra, A A; Goglia, M; Santoro, L; Santoliquido, A; Ratto, C
Abstract: Background: Arterial hyperflow to haemorrhoids has been implicated as a possible pathophysiological co-factor in haemorrhoidal disease. The purpose of this study was to investigate how transanal haemorrhoidal dearterialization (THD) can influence haemodynamic parameters at the level of the haemorrhoidal piles. Methods: Patients with grade III haemorrhoids selected for THD between July and December 2018 were evaluated using endoanal ultrasonography and colour Doppler imaging at the level of internal haemorrhoids before and 1 year after the surgical procedure. Peak systolic velocity, pulsatility index, resistivity index, acceleration time, and end-diastolic velocity were measured, and preoperative and postoperative values compared. Symptom severity was measured using a symptom-based questionnaire (score range 0–20). Results: Of 21 patients treated, 17 completed the study. Compared with preoperative values, postoperative peak systolic velocity (mean(s.d.) 18.7(1.1) versus 10.3(0.4) cm/s; P  < 0.05), pulsatility index (5.5(0.3) versus 2.8(0.4); P  < 0.050), and resistivity index (1.0(0.2) versus 0.8(0.5); P  < 0.050) decreased significantly, whereas acceleration time increased significantly (65.6(3.6) versus 83.3(4.7) cm/s 2 ; P  < 0.050); end-diastolic velocity did not change (1.9(0.2) versus 2.0(0.4); P  = 0.753). Symptoms disappeared or had improved significantly in all patients by 1 year after surgery. The mean(s.d.) total symptom severity score decreased from 15.8(1.1) to 1.2(1.6) ( P  < 0.001). Conclusion: THD affects the main haemodynamic parameters at the level of internal haemorrhoids and is associated with a decrease in arterial hyperflow. Abstract : The purpose of this observational study was to understand how transanal haemorrhoidal dearterialization (THD), a surgical approach aiming to reduce haemorrhoidal hyperflow, influences haemodynamic parameters at the level of the haemorrhoidal piles. THD affected the main haemodynamic parameters at the level of internal haemorrhoids, reducing arterial hyperflow and justifying the use of this approach to treat haemorrhoidal engorgement and bleeding.